2022
DOI: 10.3390/fermentation8080376
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Microbiota Modulation Strategies in Obesity: The Applications and Mechanisms

Abstract: Nowadays, obesity is a leading public health problem worldwide. The growing prevalence of obesity significantly accounts for other cardio-metabolic diseases, including hypertension and diabetes. Several studies have shown that obesity is strongly associated with genetic, environmental, lifestyle, and dietary factors, especially the disordered profiles of gut microbiota (GM). The present review concluded mechanistic studies and potential correspondent treatments for obesity. Specifically, the anti-obesity effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Some research indicates that the gut microbiota can influence insulin sensitivity. [ 17 ] Modulating the gut microbiota may impact insulin resistance through various mechanisms, including the production of bioactive compounds and the regulation of inflammation. [ 17 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research indicates that the gut microbiota can influence insulin sensitivity. [ 17 ] Modulating the gut microbiota may impact insulin resistance through various mechanisms, including the production of bioactive compounds and the regulation of inflammation. [ 17 ]…”
Section: Methodsmentioning
confidence: 99%
“…Comprehensive risk-benefit assessments, robust post-market surveillance, and adherence to the stringent quality standards could help eliminate the risks and to extract the immense therapeutic benefits from microbiota modulation across different patient populations. [ 17 ] The constantly changing scenario of microbiota manipulation brings in an era of great inventions, which are used for the treatment of a lot of diseases and health conditions. In the future, microbiome-based therapies, phage therapy, microbiome engineering, and the making of microbiota-targeted drugs will be among the directions for research.…”
Section: Introductionmentioning
confidence: 99%
“…13,15,17 Many review studies have shed light on different topics related to gut microbiota and obesity in the last 5 years. 8,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] However, there is still a lack of updated compilation of available data on the potential role of gut microbiota in obesity, particularly regarding dietary factors as a therapeutic approach. Therefore, this review aims to present a comprehensive and updated overview of the potential role of gut microbiota in obesity, with a special focus on dietary factors, particularly diet, prebiotics, and probiotics, as potential therapeutic options.…”
Section: Introductionmentioning
confidence: 99%
“…Although various factors can cause variations in bacterial communities (Figure 1), 14–16 there is increasing evidence that dietary modifications may be enormously effective for modulating gut microflora 13,15,17 . Many review studies have shed light on different topics related to gut microbiota and obesity in the last 5 years 8,18–36 . However, there is still a lack of updated compilation of available data on the potential role of gut microbiota in obesity, particularly regarding dietary factors as a therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%
“…SCFA has shown beneficial effects on the host metabolism, normalising glucose level and reducing plasma levels of cholesterol 7. Studies on mice have shown that increased production of SCFA by decreased Bacteroidetes and increased Firmicutes can promote obesity by increasing colonic energy availability 8. A difference in gut bacterial composition between people with severe obesity and normal weight has been shown in several studies 9 10.…”
Section: Introductionmentioning
confidence: 99%